Inequality of opportunity in developing countries: Does the income aggregate matter? - Ana Suárez Álvarez; Ana Jesús López Menéndez (Luxembourg Income Study (LIS), 2018)
The aim of this paper is to shed some light on the behaviour of Inequality of Opportunity (IOp henceforth) in developing countries. The analysis is carried out using microdata collected by national surveys and harmonised by the Luxembourg Income Study (LIS). The LIS database incorporates a wide variety of personal harmonised variables, which allow us to made cross-country comparisons for developing countries. More specifically, we analyse six countries: Brazil, Egypt, Guatemala, India, Peru and South Africa and the periods of time covered vary from 2004 to 2014. Looking back to Amartya Sen's famous question "Equality of what?" we compare IOp with economic inequality to obtain relative indicators of inequality of opportunity for each country analysed. Moreover, we use several indicators of income and consumption to assess if different aggregates lead to different conclusions both in the evolution of IOp and overall inequality and in the relative weights of the circumstances that conform IOp. In particular, we analyse IOp and Inequality for five different income aggregates: Equivalised Disposable Income using the OECD-modified scale, Personal Income, Labour Personal Income, Consumption and Monetary Consumption. We find that the use of an aggregate is not as important as it at first seems, leading in most cases to the same conclusions.
Keywords: 330